PENGARUH SENAM PRENATAL YOGA TERHADAP KESIAPAN IBU PRIMIGRAVIDA DALAM MENGHADAPI PERSALINAN DI BPM KOTA BENGKULU - yuniarti, Yuniarti; Eliana, Eliana (Politeknik Kesehatan Kemenkes Bengkulu, 2020)
Abstract: For a primigravida first face pregnancy, when the face of the delivery process tends to unpreparedness this is because labor is something new was going to happen. Practicing yoga exercises during this period is one of self-help solutions which support the process of pregnancy, birth, both physically and psychologically The purpose of this study is expected to influence prenatal yoga exercises on the readiness of labor in primigravida face BPM in Bengkulu City in 2015. This research uses quasi-experimental methods, the sampling technique with purposive sample totaling totaling 30 samples comprising 15 people carry out prenatal yoga exercises (cases) 15 people given pregnancy exercise (control). Data collection techniques directly to the two groups of pregnant women primigravidae Trimester III before the intervention were given a questionnaire to see the birth preparedness, further intervention group prenatal yoga exercises 2 times a week for 1 month, analysis of the data used test sample t test. Univariate results obtained an average yield of readiness before the intervention prenatal yoga exercises in the face of normal delivery was 19,67 after intervention decreased to 10,80, bivariate analysis obtained p value: 0,005 <α 0,05, which means there is the influence of prenatal yoga exercise on preparedness primigravida in the face of labor in BPM in the city of Bengkulu 2015. For health workers, especially midwives do prenatal yoga training exercise in pregnant women and can be taught to pregnant women for prenatal yoga exercises melakukakan useful for Preparing mother both physically and psychologically in the face of labor